Empowering consumers to purchase safe ready-to-eat chicken from street restaurants in Ouagadougou, Burkina Faso: impact of a multi-media behavior change campaign - Madjdian, D.S.; Asseldonk, M. van; Talsma, E.F.; Dione, Michel M.; Ilboudo, Guy S.; Roesel, Kristina; Grace, Delia; Knight-Jones, Theodore J.D.; Vet, E. de (Springer, 2024)
Foodborne disease resulting from food sold at urban informal markets is a major public health challenge in Sub-Saharan Africa. This study assessed the impact of an innovative nine-months multi-media campaign engaging a key influencer, aimed at empowering consumers to choose safer ready-to-eat chicken meat at informal street restaurants in Ouagadougou, Burkina Faso. A two-wave panel study assessed associations between recall of TV, radio, billboard, and social media advertisements, and self-reported behavior regarding purchasing and consumption of ready-to-eat chicken at outlets, consumer intentions, knowledge, attitudes, norms, and agency. A panel of randomly selected adult consumers (n = 852) were interviewed pre- and post-campaign, 12 months apart. 60% recalled at least one of the campaign channels when prompted. Mixed-effects models showed associations between prompted recall and feeling better informed about food safety (aOR 1.449) and increased knowledge (0.132 unit increase on total score). Social media recall was associated with higher perceived access to information (aOR 1.449) and knowledge. Billboard recall increased odds of higher perceived health benefits of paying attention to food safety behaviors when purchasing chicken (aOR 2.046). TV ad recall was associated with a 0.159 unit decrease in the gap between consumers’ intentions and behavior. An engaging consumer food safety multimedia campaign that engages key influencers improved food safety awareness and knowledge, ultimately supporting consumers to choose safer chicken at markets.